Cephalometric Features of Moyamoya Disease: A case control study - Qureshi, Adnan I (J Vasc Interv Neurol, 2014)
CONTRIBUTION OF AUTHORS: Adnan I Qureshi, Waqas I Gilani MD, Sarwat I. Gilani MD, Malik M. Adil MD . Equally assisted in the synthesis and discussion of ideas, and share equal responsibility for the information written in the manuscript above. CONFLICT OF INTEREST: No conflict of interests. RUNNING TITLE: Cephalometric Features of Moyamoya Disease BACKGROUND: Moyamoya disease is highly prevalent among patients with syndromes that have unique cephalometric characteristics such as Down syndrome. We performed a case control study to investigate the relationship between cephalometric parameters and Moyamoya disease. METHODS: Patients [aged 16-82 years] with angiographically confirmed Moyamoya disease who underwent cranial CT scan were analyzed. We identified three controls for each patient who were matched for age (±1 year), gender, and race (white or African American). The fronto-occipital diameter, bi-parietal diameter, and distance between bregma and occiput were measured from the head CT scans of cases and controls. The cephalic index was calculated by determining the ratio between bi-parietal diameter and fronto-occipital diameter and multiplying the value by 100. RESULTS: A total of 13 cases of Moyamoya disease and 39 controls were analyzed. The stage of Moyamoya disease in cases was as follows: stage 1 (n=0), stage 2 (n=1), stage 3 (n=4), stage 4 (n=2), stage 5 (n=5) and stage 6 (n=1). There was a significantly greater bi-parietal diameter in Moyamoya disease patients compared with controls (141.5±3.7 mm versus 136.9±5.4 mm, p=0.007). There was a significantly greater fronto-occipital diameter in Moyamoya disease patients compared with controls (186.5±6.5 mm versus 180.2±8.7mm, p=0.02). The distance between bregma and occiput was shorter among cases compared with controls (81.1±6.2 versus 87.5±7.0, p=0.01). CONCLUSIONS: We observed an association between cephalometric parameters and Moyamoya disease. Further study of the unique cephalometric characteristics among Moyamoya disease patients may provide additional insight into disease occurrence in white and African American populations.